THE INFLUENCE OF CUSTOMER PREFERENCES FOR MURABAHAH FINANCING PRODUCTS TOWARD PURCHASING DECISIONS AT PT PERMODALAN NASIONAL MADANI ACEH AND THEIR IMPACT ON WORD OF MOUTH - Muhammad Wazir; Sri Wahyuni (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
This study aims to analyze the influence of customers’ cultural preference factors on purchase decisions, the influence of psychological preference factors on purchase decisions, the influence of personal preference factors on purchase decisions, the influence of cultural preference factors on word of mouth, the influence of psychological preference factors on word of mouth, the influence of personal preference factors on word of mouth, the influence of cultural preference factors on word of mouth through purchase decisions, the influence of psychological preference factors on word of mouth through purchase decisions, and the influence of personal preference factors on word of mouth through purchase decisions in the ULaMM program at PT PNM Aceh Branch. This research was conducted using a quantitative approach on ULaMM product customers at PT PNM Aceh Branch. The study population consisted of all ULaMM customers, totaling 815, with a sample of 121 respondents selected through purposive sampling. The data collected were analyzed using exploratory analysis with the help of SmartPLS. The results revealed that cultural factors have a significant influence on purchase decisions, psychological factors have a significant influence on purchase decisions, and personal factors also significantly influence purchase decisions. Furthermore, cultural factors significantly influence word of mouth, psychological factors significantly influence word of mouth, and personal factors significantly influence word of mouth. Moreover, cultural factors significantly influence word of mouth through purchase decisions, psychological factors significantly influence word of mouth through purchase decisions, and personal factors significantly influence word of mouth through purchase decisions.